Analisis Proses Change Management Dengan Menggunakan Chorporate Cholesterol Test Studi Pada PT Nasmoco Pemuda Semarang - , Rizky Haidir Hullah ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research aims to analyze the Change Management Process and identify health or cholesterol level through Corporate Cholesterol Test. PT Nasmoco Pemuda Semarang became the the object of this research and all managers representing every division in the company as the sample that is Division of Sales, Marketing Section Head, Service, After Sales Service, General Affairs, Finance, and CRC. The data collection methods in this research are questionnaire, interview, observation and documentation. The results showed that Cholesterol level of PT Nasmoco quite high, from 7 divisions into the sample there are 4 divisions that have high cholesterol levels, that is Division of Sales, Marketing Section Head, Service, General Affairs, the results indicate there are diseases or problems within the company so that the company advised to make some changes related to the problems or diseases are detected on every aspect of the assessment.